O confiabilismo do agente a partir de John Greco : uma nova versão do confiabilismo goldmaniano - Fleurimond, Louis-Jacques (2015)
This study aims to present John Greco’s agent reliabilism. Acknowledging the difficulties faced by Goldman’s process reliabilism when it makes reliability the locus of justification, Greco attempts to fix this theory by ficusing on agent’s reliability rather than on reliability of the belief-forming processes, faculties, or dispositions they employ. In order to do so, Greco explores an “intellectual virtue” notion introduced in contemporary epistemology by Renest Sosa in his article “The Raft and the Pyramid”. This criterion proposed by Greco, besides being externalist, admits intuitions that are cherished by internalists and includes, therefore, responsibilist view of virtue – therefore making it a weak externalist theory. However, while Greco tries to rescue the process reliabilism theory from its problems, the agent reliabilism criterion doesn’t seem not to be free from criticism. Our purpose is twofold: first, to understand Greco’s initial motivation to propose such a criterion instead of following process reliabilism’s directions; and secondly, to understand how agent reliabilism tries to satisfy intuitions that are important to internalism.